FAKTOR - FAKTOR YANG MEMPENGARUHI EFEKTIVITAS DAN EFISIENSI SUMBER DAYA MANUSIA DI KLAPPERTAART HUIZE CAFE & RESTO BOGOR SKRIPSI - Ammar Abdulbaqi, - (2018)
This research was conducted to find out factors affecting effectivity and efficiency of Human Resources in Klappertaart Huize Café and Resto Bogor. Some methods are used for this research are descriptive research method and explanatory. Respondents are categorized into two groups, employees and company leaders. Futher interview and deep discussion are conducted to get more detail information. In this research, the author identified the factors affecting efectivity and efficiency of human resources in Klappertaart Huize Café and Resto Bogor which are : (1) variety media announcement for employee recruitment; (2) employee internship period; (3) number and frequency of employee training; (4) reward and punishment mechanisms; (5) social activities with employees; (6) variety of K3 program (Health, Safety and Environment Management System) (7) spirit and motivation of employees; (8) level of employee's satisfaction; (9) proper in using resources, (10) compliance with SOP (11) challenges from competitors;--- Penelitian dilakukan untuk mencari faktor-faktor yang mempengaruhi efektivitas dan efisiensi SDM di perusahaan Klappertaart Huize Café & Resto (KHCR) Bogor. Metode yang digunakan adalah metode deskripsi dan explanasi (explanatory). Responden dibedakan antara unsur karyawan dan pimpinan perusahaan. Diskusi lebih lanjut dan atau wawancara dilakukan untuk memperdalam informasi yang diperoleh. Dalam penelitian ini teridentifikasi faktor-faktor yang mempengaruhi efektivitas dan efisiensi SDM di KHCR Bogor ialah : (1) ragam media pengumuman rekrutmen karyawan; (2) masa orientasi karyawan baru; (3) jumlah dan frekuensi pelatihan karyawan; (4) mekanisme reward and punishment; (5) kegiatan sosial bersama karyawan; (6) ragam program K3; (7) semangat dan motivasi karyawan; (8) tingkat kepuasan karyawan terhadap pekerjaan; (9) penghematan sumberdaya; (10) kepatuhan terhadap SOP; dan (11) tantangan dari pesaing.